International policy coordination for blockchain supply chains. Issue 3 (30th May 2019) - Allen, Darcy W.E.; Berg, Chris; Davidson, Sinclair; Novak, Mikayla; Potts, Jason
Abstract: From the adoption of the shipping container to coordinated trade liberalization, reductions in trade costs have propelled modern globalization. In this paper, we analyse the application of blockchain to reduce the trade costs of producing and coordinating trusted information along supply chains. Consumers, producers, and governments increasingly demand information about the quality, characteristics, and provenance of traded goods. Partially due to the risks of error and fraud, this information is costly to produce and to maintain between dispersed parties. Recent efforts have sought to overcome these costs—such as paperless trade agendas—through the application of new technologies. Our focus is on how blockchain technology can form a new decentralized economic infrastructure for supply chains by governing decentralized dynamic ledgers of information about goods as they move. We outline the potential economic consequences of blockchain supply chains before examining policy. Effective adoption faces a range of policy challenges including regulatory recognition and interoperability across jurisdictions. We propose a high‐level policy forum in the Asia‐Pacific region to coordinate issues such as open standards and regulatory compatibility.